Performance Assessment of Laboratory IEEE 802.11 n Point-to-Multipoint Links - Carvalho, José Pacheco de (2019)
Wi-Fi based on 2.4 GHz has a large growing base of installed equipments, leading to higher interferences. Wireless communication techniques are very important in environmental contexts . Performance is a very important issue, resulting in more reliable and efficient communications. Laboratory measurements are made about several performance aspects of Wi-Fi IEEE 802.11n 5 GHz Open point-to-multipoint links. A contribution is given to performance evaluation of this technology, using available equipments (V-M200 access points from HP and WPC600N adapters from Linksys). Results are presented , namely at OSI levels 4 and 7, from TCP and UDP experiments, permitting measurements of TCP throughput versus TCP packet size, and jitter, percentage datagram loss versus UDP datagram size.